In Silico Study of Weight-selected Molecules of Sea Cucumber as Antimitotic through PyRx-Vina Approach - Broto Santoso (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
Active ligands usually have low molecular weights (MW). However, paclitaxel, a natural anticancer, has high MW. Some compounds (MW = 750-1000 dalton) in Sea cucumber from TCMSP database have anticancer activity. The objective of study is to obtain docking profile of selected compounds compared to taxol as native. Three of human kinesin-8, were collected from the RCSB database and regenerated by adding hydrogen atoms and charge using the Dock Prep in Chimera. These proteins and selected compounds were prepared to fulfil PyRx's requirement. Molecular docking was performed based on mass center value and grid-box volume from previous studies and resulted vina-score (kcal/mol). Docking data and their 3D conformation were analyzed using PyMOL, PoseView, and PLIP. The native alignment results between docked and original conformation showed that their RMSD value is less than one and only one that has the same three-dimensional conformation. Holothurinoside D, desholothurin B, and 2,4-dehydroechinoside B have a binding affinity of -9.7, -9.4, and -9.3 kcal/mol, respectively. Their value is better or at least the same as the native (-9.3 kcal/mol). Hydrophobic interactions between proteins and ligands occurred at residue of F272, V23, and P360. These results confirm that the anticancer mechanism of these compounds may be through inhibition of kinesin-8. Key words: in silico, sea cucumber, antimitotic, PyRx-vina